Effect of Finger Print Mechanisms, Procedures, and Targets on Discipline of Vocational High School Students - Ade Suryadi; Hamdun Sulaiman; Riswandi Ishak; Cep Adiwihardja; Diah Ayu Ambarsari (Sistemasi: Jurnal Sistem Informasi, 2022)
Discipline is an important factor in educating vocational high school students to achieve life goals. One indication of student discipline is attendance to take part in learning activities at school. To get graduates who have a high discipline attitude so that later they can be applied in the real world of work. In this study, several variables were used, namely the finger print mechanism, finger print procedure, finger print achievement targets and student discipline. The data collection method used a questionnaire with a sample of 50 people who were taken randomly at 3 vocational high schools. This study aims to determine how much influence the variable finger print mechanism, finger print procedure and attendance achievement targets on student discipline. student discipline. This is evidenced by (t = 3.374, 2.093) > (table = 1.66515) and P Value (Sig) = 0.000 < 0.05 while the finger print mechanism variable has no positive and insignificant effect (t = 0.226 < 1.66515) and (Sig) = 882 > 0.05.